Determinants of Millennial Employee Performance in the Banking Sector: A Case Study in West Jakarta - Didin Hikmah Perkasa; Ryani Dhyan Parashakti (Goodwood Publishing, 2025)
Purpose: This study investigates the factors influencing the performance of millennial employees, also known as Generation Y. This cohort has been shaped by significant events, including the advent of the Internet, economic liberalization, and the proliferation of social media, all of which have contributed to enhancing creativity among millennials. Research Methodology: This study used a causal quantitative design. The research model tests work attitudes, competence, job satisfaction, and job stress as independent variables, with employee performance as the dependent variable. The population and sample consisted of 60 millennial employees from banking companies located in West Jakarta, selected using saturated sampling. Data were analyzed using structural equation modeling–partial least squares, including outer model testing, inner model testing, and hypothesis testing. Results: Competence, job satisfaction, and job stress significantly affect the performance of millennial employees. Conclusions: Improving competence and job satisfaction while managing job stress is essential for enhancing millennial employee performance in West Jakarta’s banking sector. Limitations: This study is limited to a sample of 60 millennial banking employees in West Jakarta; therefore, the results may not fully represent other regions, industries, or generational groups. Contributions: This research provides empirical evidence on the key work attitude determinants of millennial employee performance and offers practical insights for HR and management in the banking sector to design competency development, satisfaction improvement, and stress management programs.